KUNYIT PUTIH DAN BUAH MENGKUDU SEBAGAI HEPATOPROTEKTOR TERKAIT KARBON TETRAKLORIDA - Suprapto Ma’at (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
Herbal remedies are prescribed for the treatment of various liver diseases including for Hepatoprotector purpose. The present study was aimed to investigate and to know the hepatoprotective activity of Curcuma zedoaria extract combined with Morinda citrifolia extract against carbon tetrachloride (CCl4) induced hepatotoxicity in rats. Liver functions were assessed by the determination of SGOT, SGPT, ALP, and bilirubin. The results of serum analysis suggest that the use of Curcuma zedoaria extract combined with Morinda citrifolia extract exhibited significant protective effect related to the hepatic damage in CCl4 induced hepatotoxicity model and further evidence of its hepatoprotective activity